KONSEP REWARD DAN PUNISHMENT DALAM PENDIDIKAN MENURUT HADIS - Sri Handayani, Ruliana Khasanah, dan Rahmi Hanifah (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2019)
Reward and punishment are methods can be applied in educating children, both given by teachers and parents. Reward is an educational reaction to the good deeds that have been done by students. Reward as a methode of motivating children to do good and improve their achievements. Reward given is a pleasant feeling thatgives rise to the desire in the child to do good and better things in the future, but not to thicken the maternal nature. In contrast to the opposite, punishment is a sanction given to the child when making mistake. In Islamic eduaction the punishment is positive, not least because they want to provide true eduaction to children so that they are aware and responsible for what they do, and do not repeat the same mistakes againKey Word : Reward, Punishment, Education, Hadis